Translation Failure from Verbal to Symbolic Representations on Contextual Mathematics Problems: Female vs Male - Rosyidin, Muhammad Ali; Rosyidi, Abdul Haris (Universitas Negeri Surabaya, 2022)
Representation translation is the ability to change one form of representation to another. This research aims to describe the failure of the translation of verbal to symbolic representations in solving contextual problems in male and female students. The research partisipant were eight students of class VII an Islamic public school at Gresik. The data collection technique is through task-based interviews. The data on the translation of verbal to symbolic representations were analyzed by unpacking the source, preliminary coordinator, constructing the target, and determining equivalence. The results showed that at the stage of unpacking the source, both male and female students experienced the same failure, namely not understanding more complex contextual problems. In the preliminary coordinator stage, male students failed to understand the requested symbolic representation, understand the meaning of mathematical symbols, and determine keywords, while female students only failed due to their mistakes in the previous stage. In the constructing the target stage, male students failed to construct a symbolic representation of the plans made and translate into mathematical symbols, while female students failed to translate verbal words into mathematical symbols and mathematical operations. At the determining equivalence stage, male and female students have not been able to do it.